Group self-build housing: A bottom-up approach to environmentally and socially sustainable housing. (10th January 2020) - Heffernan, Emma; Wilde, Pieter de
Abstract: In England, there is a longstanding and increasing undersupply of both affordable and open-market housing. Around three quarters of all new homes in the UK are currently built speculatively by the developer-led private housing sector. However, demand for self-build housing is growing. Concurrently, there is also a need to address the sustainability of homes, which represent 29% of final energy consumption in the UK. There is a clear imperative to develop business models within the construction sector in which both social and environmental sustainability are inherent. The aim of this paper is to explore professional and expert opinions on the suitability of group self-build housing as a development model for zero carbon homes. A Policy Delphi study was conducted both at a national level in England and at a regional level in South West England. In this iterative, non-contact research method, online questionnaires were used to gather data from the same panellists over three rounds. Panellists were drawn from seven groups: public sector, specialist groups/experts, housing associations, housing developers, designers, contractors, and financial institutions. The findings highlight that the panellists believe that group self-build is well suited as a development model for the delivery of zero carbon homes and sustainable communities. The advantages identified include: energy efficiency, affordability, quality, innovation, and sustainable communities.